Quantum geometry of chiral bosons on a circle - Reyes Martinez, J. R. [UNESP]; Zimerman, A. H. [UNESP]; Teotônio Sobrinho, P. (American Physical Society (APS), 1989)
We extend the geometric treatment done for the Majorana-Weyl fermions in two dimensions by Sanielevici and Semenoff to chiral bosons on a circle. For this case we obtain a generalized Floreanini-Jackiw Lagrangian density, and the corresponding gravitational (or Virasoro) anomalies are found as expected. © 1989 The American Physical Society.